2019
DOI: 10.3892/mmr.2019.10092
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the interaction between intrauterine adhesion and vaginal microbiota using high‑throughput sequencing

Abstract: Intrauterine adhesion (IUA) is one of the most common diseases of the reproductive system. Due to the high postoperative recurrence rate of IUA, it is crucial to identify the possible causes of pathogenesis and recurrence of this disease. In the present study, a high-throughput sequencing approach was applied to compare the vaginal microbiota between healthy women [healthy vaginal secretion (HVS) group] and patients with IUA [intrauterine adhesion patients' vaginal secretion (IAVS) group]. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
3
26
3
Order By: Relevance
“…Theαvalue was set to 0.05 in order to correct multiple comparisons. Finally, we used Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) to analyze the metabolic function and its influence on the host cell of bacteria in Kyoto Encyclopedia of Genes and Genomes (KEGG) functional spectrum database ( Liu et al., 2019 ; Zheng et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Theαvalue was set to 0.05 in order to correct multiple comparisons. Finally, we used Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) to analyze the metabolic function and its influence on the host cell of bacteria in Kyoto Encyclopedia of Genes and Genomes (KEGG) functional spectrum database ( Liu et al., 2019 ; Zheng et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another example is represented by the patients with IUAs where significant differences at the phylum and genus level were observed (more precisely, a significant reduction in Firmicutes and Lactobacillus , to the detriment of Actinobacteria, Gardnerella , and Prevotella [ 50 ]. The presence of, and subsequent infections caused by, Mycobacterium tuberculosis is also detrimental.…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…IUA refers to the injury of the basal layer of endometrium caused by pregnant or nonpregnant uterine trauma and even complete occlusion of the uterine cavity or cervix, such as secondary amenorrhea, periodic abdominal pain, recurrent abortion, and infertility [ 13 , 14 ]. Previous studies have confirmed that the expression of miR-543 is downregulated in IUA and negatively regulates CDH2 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%